Meningkatkan Motivasi Belajar Siswa SD Melalui Metode Pembelajaran Interaktif - Ferdy Fahrurrazi; Sri Setia Putra Jayawardaya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to increase the learning motivation of elementary school students through the application of interactive learning methods. Interactive learning methods are believed to be able to stimulate students' interest and active participation in the teaching and learning process. We conducted this research using a quantitative approach by applying an experimental design. Data was collected through questionnaires and observations of fourth and fifth grade students in one of the elementary schools in Padang. The results showed that the use of interactive learning methods significantly increased students' learning motivation. The conclusion of this study confirms the importance of integrating interactive learning methods in the primary education curriculum to encourage student engagement and motivation.